The existence of international law in inter-state conflict - Fadli Andi Natsif (Indonesia Prime, 2019)
In conducting interactions or relations between countries does not cover the likelihood of conflict between them. International law, as one of the legal instruments governing inter-country relations, expected to play a role in settling in the event of a conflict. Based on the method of normative studies by conducting a search technique of various literature or books, it can be concluded that international law as a legal system for which countries highly determine the enforcement of its validity. The International Court, as a judicial institution, only has jurisdiction if countries agree jointly to resolve conflicts suffered by these countries